2017
DOI: 10.1002/1873-3468.12548
|View full text |Cite
|
Sign up to set email alerts
|

Split‐BioID: a proximity biotinylation assay for dimerization‐dependent protein interactions

Abstract: The biotin identification (BioID) protocol uses a mutant of the biotin ligase BirA (BirA*) fused to a protein-of-interest to biotinylate proximate proteins in intact cells. Here, we show that two inactive halves of BirA* separately fused to a catalytic and regulatory subunit of protein phosphatase PP1 reconstitute a functional BirA* enzyme upon heterodimerization of the phosphatase subunits. We also demonstrate that this BirA* fragment complementation approach, termed split-BioID, can be used to screen for sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 25 publications
0
70
0
1
Order By: Relevance
“…Alternatively, tagging through genome editing would ensure physiological expression levels. Of note, as we observed stronger re-activation with our split-BioID assay based on the E256/G257 splitting site than with the alternative E140/Q141 splitting site12, it will most probably be better suited when low expression levels of the fusion proteins are desired.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Alternatively, tagging through genome editing would ensure physiological expression levels. Of note, as we observed stronger re-activation with our split-BioID assay based on the E256/G257 splitting site than with the alternative E140/Q141 splitting site12, it will most probably be better suited when low expression levels of the fusion proteins are desired.…”
Section: Discussionmentioning
confidence: 76%
“…This lower activity was sufficient for performing BioID experiments (see below). A recent study also described a PCA based on two BirA* fragments using an alternative splitting site (E140/Q141)12. We wondered if this splitting site would perform similar to our PCA.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Novel or improved applications using BioID ligase have spurred numerous follow-up articles including a smaller version of BioID with improved sensitivity and localization (22), its use for identifying protein-RNA interactions (23), split-BioID studies (24,25), and faster versions of BioID (26). Several conventional approaches have been utilized to stably introduce BioID-fusion proteins to cells including transfection (7), viral infection (27), and more recently, CRISPR-Cas9 (28).…”
Section: Introductionmentioning
confidence: 99%
“…This proximal biotinylation has been successfully used to identify novel protein interactions [see reviews: 4, 9], and has been shown as complementary to traditional affinity purification approaches [10]. Interests in this approach have led to improved variants of BioID proteins: BioID2, a smaller biotin ligase from Aquifex aeolicus [11], and a split-BioID as a dimerization dependent biotin ligase [12, 13]. …”
Section: Introductionmentioning
confidence: 99%